Education in bioethics and citizenship formation - Carvajal Abril, Haywer Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article aims to make an analysis of the conceptual foundations in Nussbaum and Cortina’s work, according to which education in bioethics can be used to promote the exercise of citizenship in undergraduates. In order to successfully carry out this research, in the first part it is developed a reflection on what bioethics is, and more specifically education in bioethics. The second and third sections show a reflection on the conceptual elements of Nussbaum and Cortina which could be used by education in bioethics for citizenship formation. Finally, such elements and their importance to bioethics are analyzed.